СУҒОРИЛАДИГАН АРЗИҚ – ШОХЛИ ТУПРОҚЛАРНИНГ АНТРОПОГЕН ОМИЛ ТАЪСИРИДАГИ ЭВОЛЮЦИЯСИ (Scientific journal of the Fergana State University, 2023)
This article deals with role of the anthropogenic factor in the process of modern evolutionary development of irrigated meadow saz soils in Central Fergana